2017
DOI: 10.3389/fcomm.2017.00007
|View full text |Cite
|
Sign up to set email alerts
|

“Tree Is Life”: The Rising of Dualism and the Declining of Mutualism among the Gedeo of Southern Ethiopia

Abstract: This study investigates ecocultural discourses and practices among the Gedeo in southern Ethiopia within the contexts of globalizing commodification of nature, successive governmental extractivist and conservationist discourses, and increasingly influential colonial present religious systems. Our analysis illustrates ways in which indigenous Gedeo understandings of reciprocal ecological coexistence are rooted in cultural knowledge, values, and customs. However, competing forms of knowledge introduced in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…However, focus group members of the upstream region have underlined the decline of native knowledge as well as the steady rise of environmental degradation has substantially contributing to the challenges to manage agroforests. Legesse [28] and Debelo et al [33] reported that elders worry about the ongoing transformation of the core Gedeo principles of "tree is life" to the increasingly predominant view, especially among Gedeo youth, that "tree is money in the pocket". This scenario also confirmed that upstream farmers highly valued woodlot/construction service (ranked 3rd), a reflection of the extensive tree extraction practices carried out mainly to earn money.…”
Section: Spatial Variations Of Community Values and Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, focus group members of the upstream region have underlined the decline of native knowledge as well as the steady rise of environmental degradation has substantially contributing to the challenges to manage agroforests. Legesse [28] and Debelo et al [33] reported that elders worry about the ongoing transformation of the core Gedeo principles of "tree is life" to the increasingly predominant view, especially among Gedeo youth, that "tree is money in the pocket". This scenario also confirmed that upstream farmers highly valued woodlot/construction service (ranked 3rd), a reflection of the extensive tree extraction practices carried out mainly to earn money.…”
Section: Spatial Variations Of Community Values and Threatsmentioning
confidence: 99%
“…Hence, it has been recommended as a novel strategy for Africans to curb ecosystem ruin [32]. Thanks to its widely recognized ecosystem repairs and productivity potentials, the Gedeo agroforestry land use is nowadays in the process of inscription into UNESCO world heritage sites [33]. We believe that such distinctive and diverse landscapes, with associated culture-bound knowledge systems about landscape management, needs to be studied and documented.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these practices are recommended as a novel strategy for African countries to curb ecosystem degradation [27]. Recognizing its ecosystem maintenance and productivity potential, Gedeo's (The dominant tribe inhabited the upstream study region and well known for practicing agroforestry systems) traditional agroforest is now in the process of becoming a UNESCO world heritage site [28]. Information on these distinctive and diverse landscapes, with their associated culture-bound knowledge systems concerning the management of landscape diversity, must be studied and documented.…”
Section: Introductionmentioning
confidence: 99%
“…Ethiopia loses about 141,000 hectares of natural forests each year due to firewood collection, conservation of farmland, overgrazing and use of wood for building material (Oljirra 2019). Cultural factors: Ecoculture transformation: Empirical research made by Regassa et al (2017) in the Gedeo zone, Southern part of Ethiopia described that the Gedeo experienced extensive ecocultural transformations after they became part of greater Ethiopia in the early twentieth century. Also, their study argued, the Gedeo youth, engaged in cutting trees for firewood, charcoal, and construction materials, and the truck drivers, loading the resulting lumber to sell in nearby towns.…”
Section: Technological Factorsmentioning
confidence: 99%